Analysis of the Nurse’s Behavior toward Helping a Patient with a Mental Health Problem: A Systematic Review - Darni Darni; Siti Khadijah; Sitti Sulaihah (Jurnal Ners, 2019)
Background: Nurses have the role of helping in the healing process of patients through their knowledge, attitudes and actions. Several studies have shown that nurses frown when serving patients and this worsens the patient’s condition. The aim of this study was to analyze about nurse behavior towards people with mental disorder.Method: The articles were obtained from a search through the Scopus, Google Scholar, Science Direct and Proquest database.Result: Article searches began in 2014 until 2018 and found 8 article which match the inclusion criteria. After the articles were obtained, a study was then carried out up until the stage of making a systematic review.Conclusion: The behavioral interventions of the mental health nurse will improve and accelerate the recovery of the patients with mental disorders.